Effect of small sided handball game on aerobic capacity and repeated sprint ability of male handball players - Balasubramanian Chıttıbabu (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to determine the effects of four and eight weeks small-sided handball game on aerobic capacity and repeated sprint ability of male handball players. Sixteen (16) male university handball players volunteered to act as subjects and were randomly assigned to small-sided handball game group (SSHG) and control group (CG).  Small-sided handball game was administered three days in a week for eight weeks. Subjects were measured on aerobic capacity, total sprint time and fatigue index on three occasions first before administration of training as pre-test, after four weeks of training as mid test and after eight weeks of training as post-test. A two-way repeated measure ANOVA with last factor repeated revealed that aerobic capacity, total sprint time and fatigue index improved (p lt;0.05). Aerobic capacity showed an improvement of 4.75% after four weeks and 8.83% % after eight weeks of small-sided handball game training in male handball players. Similarly, total sprint time and fatigue index also decreased 4.19% and 34.9 % only after eight weeks of training but after four weeks no changes is observed. This study shows that small-sided handball game (4 vs. 4) is effective in improving aerobic capacity in four and eight weeks of training but total sprint time and fatigue index elicited changes only after eight weeks.